KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS VII MTs NEGERI 4 BUTON - Atika Salmawati; Sri Suryana Dinar; Saidiman (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The primary focus of this research is to analyze the ability of grade VII MTs Negeri 4 Buton in writing procedural texts. The objective of this study is to describe the writing skills of procedural texts among VII grade students of MTs Negeri 4 Buton. This research is categorized as field research using a quantitative descriptive method. The population of this study consists of all VII grade students at MTs Negeri 4 Buton, totaling 52 students, who were also used as the sample. The instrument used to collect data was a written test that measured students' ability to write procedural texts. Based on the research results and data analysis, it was found that out of 52 VII grade students at MTs Negeri 4 Buton, 36 students (69.23%) were categorized as able to write procedural texts individually, while 16 students (30.76%) were categorized as unable. Classically, the writing ability of procedural texts among VII grade students at MTs Negeri 4 Buton is categorized as unable. This is because the ability of individual students who meet the criteria for achieving learning objectives (KKTP) of 70% is only 62.23%. This does not meet the classical mastery criteria of 85%. This can be seen in the students' scores in the research. The ability to write procedural texts, which includes aspects such as the title of the procedural text (82.69%), the relevance of the content of the procedural text (94.23%), the structure of the procedural text (71.15%), the linguistic features of the procedural text (26.92%), and the mechanics of spelling the procedural text (19.23%), shows that out of the six aspects assessed, one aspect is categorized as capable, namely the relevance of the content, while the other four aspects are categorized as less capable.